2009
DOI: 10.1111/j.1476-5381.2009.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of exhaled hydrogen sulphide gas in rats exposed to intravenous sodium sulphide

Abstract: Background and purpose: Sodium sulphide (Na2S) disassociates to sodium (Na + ) hydrosulphide, anion (HS -) and hydrogen sulphide (H2S) in aqueous solutions. Here we have established and characterized a method to detect H2S gas in the exhaled breath of rats. Experimental approach: Male rats were anaesthetized with ketamine and xylazine, instrumented with intravenous (i.v.) jugular vein catheters, and a tube inserted into the trachea was connected to a pneumotach connected to a H2S gas detector. Sodium sulphide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 47 publications
(85 reference statements)
3
60
0
Order By: Relevance
“…This approach, which differs from traditional amperometry, relies on a certain number of prerequisites and limits. We found that the RM17-1000b hydrogen sulfide detector, which was previously used to estimate the rate of elimination of H 2 S by the lungs (29), is sensitive to change in humidity, which would require it to re-zero when connected to expired gas unless dry gas is used. Second, the sampling flow of these analyzers is high (around 0.5 l/min, which is about 2 times the minute ventilation of a rat) but does fluctuate around its set value.…”
Section: What Was Measured In the Blood?mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach, which differs from traditional amperometry, relies on a certain number of prerequisites and limits. We found that the RM17-1000b hydrogen sulfide detector, which was previously used to estimate the rate of elimination of H 2 S by the lungs (29), is sensitive to change in humidity, which would require it to re-zero when connected to expired gas unless dry gas is used. Second, the sampling flow of these analyzers is high (around 0.5 l/min, which is about 2 times the minute ventilation of a rat) but does fluctuate around its set value.…”
Section: What Was Measured In the Blood?mentioning
confidence: 99%
“…In the current study, following experiments from Insko et al (29) and Wintner et al (54), we infused H 2 S intravenously in the form of NaHS to spontaneously breathing, urethane-anesthetized rats. We increased the infusion rate gradually until an apnea occurred ("lethal" exposure).…”
mentioning
confidence: 99%
“…In contrast, patients with exacerbations of COPD have significantly decreased levels of serum H 2 S. Thus, levels of endogenous H 2 S may represent a potential indicator of COPD severity. [9][10][11] However, the relationship between levels of exhaled H 2 S and airway or systemic inflammation has not yet been determined. Recently, the analysis of signaling molecules present in exhaled air has become a popular technique for noninvasive assessment of airway inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In in vivo conditions (37°C, pH ϳ7.4), H 2 S is predicted to exist as 14% free H 2 S gas, 86% HS Ϫ , and trace levels of S 2Ϫ (96,153). Limitations to measuring H 2 S include 1) free H 2 S has a short half-life, ranging from 12 to 300 s in various species, and 2) detection methods may release bound sulfur from proteins, resulting in increased H 2 S concentrations (61,96,142,153).…”
mentioning
confidence: 99%
“…Although the intermediate pathways involved in the oxidation of H 2 S are not completely understood, sulfate is the primary by-product of sulfide catabolism, which may be excreted in the urine and feces (63,69,90). An additional pathway for excretion of H 2 S may include expiration by the lungs (61,142). H 2 S may be scavenged by disulfide-containing molecules and red blood cells, where H 2 S binds to methemoglobin forming sulfhemoglobin, which is oxidized to thiosulfate (147).…”
mentioning
confidence: 99%